Leak Monitoring in Split Duct Air Conditioner Based on Internet of Things - Aji, Eka Afdi Septiyono; Jamaaluddin, Jamaaluddin; Ahfas, Akhmad; Ayuni, Shazana Dhiya (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2023)
Water accumulation in air conditioning (AC) drain pans can lead to corrosion and subsequent leaks, impacting AC system performance. This study focuses on implementing a monitoring system to track water levels and promptly discharge water to prevent corrosion. Using a research and development approach, the study evaluated the water level sensor's performance in measuring water levels and the pump's effectiveness in discharging water at specific levels, ensuring overall system reliability. The system utilized the NodeMCU ESP8266 microcontroller, a water level sensor, an LCD I2C 16x2 display, and Blynk as a smartphone-based monitoring platform. The findings demonstrated the effective functionality of the device in evacuating accumulated water from the AC evaporator. This was achieved through the activation of a water pump when the water level reached a threshold of 2 cm, thereby preventing potential leakage in the air conditioner's storage gutter.